2017
DOI: 10.1073/pnas.1619302114
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy, long-term toxicity, and mechanistic studies of gold nanorods photothermal therapy of cancer in xenograft mice

Abstract: Gold nanorods (AuNRs)-assisted plasmonic photothermal therapy (AuNRs-PPTT) is a promising strategy for combating cancer in which AuNRs absorb near-infrared light and convert it into heat, causing cell death mainly by apoptosis and/or necrosis. Developing a valid PPTT that induces cancer cell apoptosis and avoids necrosis in vivo and exploring its molecular mechanism of action is of great importance. Furthermore, assessment of the long-term fate of the AuNRs after treatment is critical for clinical use. We firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
208
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 259 publications
(214 citation statements)
references
References 85 publications
3
208
0
3
Order By: Relevance
“…Discussion Current advances of nanoscience and nanomedicine enable us to fabricate "intelligent" nanomaterials that can specifically target cellular and subcellular locations in living animals for treating diseases (84,85). Although larger nanoparticles (>18 nm in diameter) can accumulate in organs such as the liver and spleen and be eliminated slowly (86), the long-term effect of AuNRs in mice shows no toxic effect after 15 mo (87). The biocompatibility and special physicochemical properties of AuNRs provide us an effective and safe potential treatment of cancer.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Discussion Current advances of nanoscience and nanomedicine enable us to fabricate "intelligent" nanomaterials that can specifically target cellular and subcellular locations in living animals for treating diseases (84,85). Although larger nanoparticles (>18 nm in diameter) can accumulate in organs such as the liver and spleen and be eliminated slowly (86), the long-term effect of AuNRs in mice shows no toxic effect after 15 mo (87). The biocompatibility and special physicochemical properties of AuNRs provide us an effective and safe potential treatment of cancer.…”
Section: Resultsmentioning
confidence: 99%
“…Our previous study has shown success in treating xenograft mice and natural mammary gland tumors in dogs and cats using AuNRassisted PPTT, where no cancer relapse or metastasis occurred in any of the test subjects (87,88), implying the potential effect of AuNRs in inhibiting cancer metastasis. We also designed nuclear membrane-targeted AuNPs for inhibiting cancer cell migration and invasion, by mechanically increasing their nuclear stiffness, with greatly reduced AuNP dosage (26).…”
Section: Integrinmentioning
confidence: 97%
“…Although, our man‐GNR‐siRNA is highly effective for DC‐targeted delivery of siRNA and GNR has been demonstrated to be safe in the long term in vivo , there are many aspects that deserve more in‐depth study before the wide clinical applications of nanomaterials. For example, the metabolism and distribution of nanomaterials in the body, dosages for administration and so on, especially in the context of biocompatibility, need more in‐depth investigations, including for the first‐in‐class man‐GNR‐siIDO reagent described in our study …”
Section: Discussionmentioning
confidence: 99%
“…In PPTT, AuNRs that absorb the incident near infra-red (NIR) light to induce heat, and thereby could trigger tumor apoptosis. 14,15 AuNRs-PPTT has been applied successfully on treating tumor bearing mice, cats and dogs. In these studies, we observed that animals with induced or spontaneous tumors were effectively cured with no tumor reoccurrence or metastasis.…”
mentioning
confidence: 99%